It Only Looks the Same From a Distance: How U.S., Finnish, and Irish Schools Support Struggling Readers. Issue 8 (16th November 2016) - Miller, Samuel; Budde, Melissa Adams; Massey, Dixie; Korkeamäki, Riku; Kennedy, Eithne; O'Rourke, Maria; Korkeamäki, Riitta-Liisa
Abstract : This study examined how U.S., Finnish, and Irish educators identified and supported struggling readers. Using Johnston's (2011) framework for evaluating reading interventions and activity theory (Engeström, 1999), we interviewed educators in four U.S., three Irish, and three Finnish schools. In the United States, the adoption of three beliefs—reductionist reading philosophy, difficulties as cognitive and remediated through instruction, and reading problems as unexpected phenomena—reinforced a skills-driven approach. Irish and Finnish educators adopted a more holistic view of reading, and teachers used formative assessment to support struggling students over extended periods while working collaboratively with other staff. Discussion focuses on how these beliefs influenced divisions of labor, roles and responsibilities, and the urgency with which difficulties were addressed.